Sistem pengawalan suhu dan kelembapan relatif rumah cendawan - Sulaiman, Nurulhana (2013)
Mushroom cultivation is influenced by factors such as environmental temperature, humidity, light, and air flow in mushroom houses. Between factors of the basic needs, environmental temperature and humidity is the most important factor affecting productivity the mushrooms. The current state of the mushroom farm, temperature and humidity controlling is done manually by wetting the floor of mushroom houses. Problems often occur with manual systems is the difficulty of mushroom operators to ensure the appropriate temperature and humidity according to the expansion phase of the fungus. Controlling system temperature and humidity in mushroom house "SMART Climate Control" is a control system developed for the purpose of controlling the temperature and humidity in mushroom houses. System used to control the temperature and humidity is specific for each growth phase of the fungus. In addition, by using this system users will be able to see the latest of temperature and humidity, display reports, graphs, the status of actuator and version system. Therefore, in the hope that by using system can be minimize the time for the production and improve operational effectiveness in the field. Use of this system is also able to reduce labor costs and improve the management efficiency for the largest scale farms.